2010
DOI: 10.1007/s10661-010-1439-y
|View full text |Cite|
|
Sign up to set email alerts
|

Benefits of Bt cotton counterbalanced by secondary pests? Perceptions of ecological change in China

Abstract: In the past, scientific research has predicted a decrease in the effectiveness of Bt cotton due to the rise of secondary and other sucking pests. It is suspected that once the primary pest is brought under control, secondary pests have a chance to emerge due to the lower pesticide applications in Bt cotton cultivars. Studies on this phenomenon are scarce. This article furnishes empirical evidence that farmers in China perceive a substantial increase in secondary pests after the introduction of Bt cotton. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 27 publications
0
46
1
4
Order By: Relevance
“…Nonetheless in Switzerland, use of synthetic insecticides against corn borers is rare (Albisser Vögeli et al 2011) making deployment of Bt maize unlikely to be a reasonable option for farmers (Meissle et al 2011). Noteworthy, secondary pests may also appear, like the western bean cutworm Striacosta albicosta, that are not affected by Cry1Ab (Zhao et al 2011;Catarino et al 2015).…”
Section: Gm Crops Marginally Improve Environmental Sustainabilitymentioning
confidence: 99%
“…Nonetheless in Switzerland, use of synthetic insecticides against corn borers is rare (Albisser Vögeli et al 2011) making deployment of Bt maize unlikely to be a reasonable option for farmers (Meissle et al 2011). Noteworthy, secondary pests may also appear, like the western bean cutworm Striacosta albicosta, that are not affected by Cry1Ab (Zhao et al 2011;Catarino et al 2015).…”
Section: Gm Crops Marginally Improve Environmental Sustainabilitymentioning
confidence: 99%
“…2008;Li et al 2011;García et al 2012;Tian et al 2013). A resurgence of secondary pests such as aphids, spider mites, and mirid bugs has also been reported in transgenic crops (Wu et al 2002;Lu et al 2010;Zhao et al 2011). The effect of transgenic crops on the life histories of non-targeted insects has been observed under laboratory conditions, but the results are inconsistent.…”
Section: Articlementioning
confidence: 99%
“…Among these species, T. turkestani is a damaging and important pest (Guo et al 2013), also it causes the most damage to cotton in the northern part of the Xinjiang Uyghur Autonomous Region (Lu, 1990). Spider mite populations have increased since the widespread adoption of transgenic cotton (Wu and Guo, 2005;Zhao et al 2011). In some cases, spider mites have become the primary pest of transgenic cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already reported that the adoption of Bt crops leads to a reduction in insecticide use (Hutchison et al 2010;Kouser and Qaim 2011;Lu et al 2012), possibly favoring certain nontarget pest outbreaks (Zhao et al 2011). Therefore, it is important to understand the direct and indirect impacts of Bt plants on both non-target pest species and their natural enemies.…”
Section: Introductionmentioning
confidence: 99%